RELATIONSHIP OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, AND INTEGRATING PERSONAL INNOVATIVENESS IN INFORMATION TECHNOLOGY (PIIT) WITH THE INTENTION TO USE MOOCS CONTINUOUSLY USING THE TECHNOLOGY ACCEPTANCE MODEL - Saad Alghamdi; Ben Soh La (Proceedings on Engineering Sciences, 2023)
This study assesses the adoption of Massive Open Online Courses (MOOCs) by Saudi students in Australian universities, exploring its potential impact on achieving Saudi Vision 2030 goals. Utilizing the Technology Acceptance Model, integrated with Personal Innovativeness in Information Technology (PIIT), the study examines the intention to continuously use MOOCs through Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and PIIT. Four hypotheses were validated with survey responses from 141 Saudi students, revealing correlations between demographic factors, learning benefits, and technology adoption. Male students aged 25 to 44, pursuing diverse courses, exhibited a higher likelihood of continuous MOOC adoption. The majority (65-75%) found MOOCs instrumental in various learning tasks, emphasizing ease of use and control. These capabilities fostered a willingness to explore new technologies promptly. Despite hesitations among some students, a significant majority expressed a readiness to predict, plan, and intend to use MOOCs continuously. The study recommends strategies to enhance MOOC adoption in Saudi Arabia, targeting students, faculty, university management, the Ministry of Education, and the government, aligning with Vision 2030 objectives. Acknowledging study limitations, these findings provide valuable insights for future research and initiatives in the evolving landscape of online education.